Actitudes y creencias en la comprensión de textos escritos en inglés en estudiantes de tercer grado de secundaria en instituciones educativas públicas del distrito de Iquitos 2021 - Torres Grandez, Gabriela Francisca (2023)
The objective of this study was to explain the influence of attitudes and beliefs on third year students’ English reading skills at public high schools of Iquitos district 2021. The research type was explanatory with field study, contemporary transectional, multivariate designs. The study population was made up by 2,626 students and a stratified sample with proportional allocation of 335 students. The results showed that the mean score in reading was 10.96, out of 20, which is at a beginner level of achievement; as well as in its dimensions: Getting information (10.93), inference and interpretation of information (10.87), text content, context and format evaluation (11.07). Results show that the mean score of attitudes and beliefs was 61.55 and 51.08, respectively, on a scale transformed to 100. The correlation indexes in the variable’s attitudes and beliefs with reading skills were r = -0.021 and r = - 0.093, with p-value is 0.700 > α = 0,05 and 0.088 > α = 0.05 respectively. In conclusion, as correlation was inexistent, there was no need to analyze contingency, therefore, there is no influence of attitudes and beliefs on English reading skills in the study population students, rejecting the working hypothesis.